Genetic analysis of a phosphatidylinositol 3-kinase SH2 domain reveals determinants of specificity. - Yoakim, M (1994)
Phosphatidylinositol 3-kinase is an important element in both normal and oncogenic signal transduction. Polyomavirus middle T antigen transforms cells in a manner depending on association of its tyrosine 315 phosphorylation site with Src homology 2 (SH2) domains on the p85 subunit of the phosphatidylinositol 3-kinase. Both nonselective and site-directed mutagenesis have been used to probe the interaction of middle T with the N-terminal SH2 domain of p85. Most of the 24 mutants obtained showed reduced middle T binding. However, mutations that showed increased binding were also found. Comparison of middle T binding to that of the platelet-derived growth factor receptor showed that some mutations altered the specificity of recognition by the SH2 domain. Mutations altering S-393, D-394, and P-395 were shown to affect the ability of the SH2 domain to select peptides from a degenerate phosphopeptide library. These results focus attention on the role of the EF loop in the SH2 domain in determining binding selectivity at the third position after the phosphotyrosine.